Optimization and reflexivity in interdisciplinary agri-environmental scholarship - Chiles, Robert Magneson; Drohan, Patrick J.; Cibin, Raj; O'Sullivan, Lilian; Doody, Donnacha; Schulte, Rogier P. O.; Grady, Caitlin; Jiang, Fei; Preisendanz, Heather E.; Dingkuhn, Elsa L.; Veith, Tamie L.; Anderson, Aine (Frontiers in Sustainable Food Systems, 2023)
The Chesapeake Bay and Upper Bann watersheds in the United States and Northern Ireland, respectively, exemplify how agricultural systems contribute to groundwater and surface water pollution, which leads in turn to water quality issues in downstream water bodies. Interdisciplinary research, public outreach, and stakeholder engagement have received increased attention and consideration as pragmatic approaches for addressing these types of complex agri-environmental dilemmas. However, such approaches are far from guaranteed to improve water quality, as political-economic constraints, power asymmetries, cultural differences, divergent incentives, research gaps, and personality differences all complicate the process, and this can ultimately impact water quality efforts. We present a holistic approach to addressing these challenges in the Chesapeake Bay and Upper Bann watershed management efforts by integrating the methodological strategies of optimization and reflexivity. Our work thus provides a behind-the-scenes perspective on how interdisciplinary teams can improve their cooperation efficiency when addressing complex agri-environmental issues.